Proposal for a new clinical entity, IgG4-positive multiorgan lymphoproliferative syndrome: analysis of 64 cases of IgG4-related disorders. Issue 8 (13th August 2008) - Masaki, Y; Dong, L; Kurose, N; Kitagawa, K; Morikawa, Y; Yamamoto, M; Takahashi, H; Shinomura, Y; Imai, K; Saeki, T; Azumi, A; Nakada, S; et al.
Abstract : Background: Mikulicz's disease (MD) has been considered as one manifestation of Sjögren's syndrome (SS). Recently, it has also been considered as an IgG4 -related disorder. Objective: To determine the differences between IgG4 -related disorders including MD and SS. Methods: A study was undertaken to investigate patients with MD and IgG4 -related disorders registered in Japan and to set up provisional criteria for the new clinical entity IgG4 -positive multiorgan lymphoproliferative syndrome (IgG4 +MOLPS). The preliminary diagnostic criteria include raised serum levels of IgG4 (>135 mg/dl) and infiltration of IgG4 + plasma cells in the tissue (IgG4 +/IgG+ plasma cells >50%) with fibrosis or sclerosis. The clinical features, laboratory data and pathologies of 64 patients with IgG4 +MOLPS and 31 patients with typical SS were compared. Results: The incidence of xerostomia, xerophthalmia and arthralgia, rheumatoid factor and antinuclear, antiSS-A/Ro and antiSS-B/La antibodies was significantly lower in patients with IgG4 +MOLPS than in those with typical SS. Allergic rhinitis and autoimmune pancreatitis were significantly more frequent and total IgG, IgG2, IgG4 and IgE levels were significantly increased in IgG4 +MOLPS. Histological specimens from patients with IgG4 +MOLPS revealed marked IgG4 + plasma cell infiltration. Many patients with IgG4 +MOLPS had lymphocytic follicle formation, but lymphoepithelial lesions were rare. Few IgG4 + cells were seen in the tissue of patients with typical SS. Thirty-eight patients with IgG4 +MOLPS treated with glucocorticoids showed marked clinical improvement. Conclusion: Despite similarities in the involved organs, there are considerable clinical and pathological differences between IgG4 +MOLPS and SS. Based on the clinical features and good response to glucocorticoids, we propose a new clinical entity: IgG4 +MOLPS.